Sanitation situations in selected Southeast Asian countries and application of innovative technologies - Koottatep, Thammarat; Chapagain, Saroj Kumar; Polprasert, Chongrak; Panuvatvanich, Atitaya; Ahn, Kyu-Hong (SPRINGER, 2018)
Sanitation coverages in selected Southeast Asian countries, namely Myanmar, Thailand and Vietnam, were increased from 1990 to 2015. The toilet coverage of 96, 100 and 99% was reported in Myanmar, Thailand and Vietnam, respectively. On contrary, incidences of waterborne disease and water pollution are still in existence. This situation is due mainly to poor design, performance and maintenance of the dominantly used on-site sanitation systems (OSS) such as septic tanks, cesspools. In addition, fecal sludge (FS), which has to be emptied from these OSS, is not properly managed. There are lacks in rules and regulation on FS management (FSM). Recent research conducted at the Asian Institute of Technology, Thailand, involved the development of innovative OSS, namely solar septic tanks, Zyclone cube toilet and septic tank effluent treatment units. The operation of solar septic tanks with increased temperatures of 40-50 degrees C could inactive E. coli by 4-6 logs in the effluent. The solar septic tanks enhanced the microbial degradability with increased methane gas production and reducing fecal sludge accumulation by 50%. The Zyclone cube toilet separated the toilet wastewater into solid and liquid portions, which were treated by heating and electrochemical disinfection, respectively. The septic tank effluent was further treated by a unit consisting of granular activated carbon coated with nano-silver resulting in E. coli reduction of 5-6 logs. These technologies should be applied for OSS in Southeast Asian and other developing regions for environmental improvement and public health protection.
Keywords: SEPTIC TANKS; INACTIVATION